1997
DOI: 10.3171/jns.1997.87.2.0294
|View full text |Cite
|
Sign up to set email alerts
|

The complement membrane attack complex and the bystander effect in cerebral vasospasm

Abstract: Activation of complement results in formation of membrane attack complexes (MACs) that can insert themselves either into cells that initiate complement activation or into nearby ("innocent bystander") cells. The MACs form large-conductance, nonspecific ion channels that can cause lytic or sublytic cell damage. The authors used a highly sensitive patch clamp technique to assess the contribution of the bystander effect to the pathophysiology of cerebral vasospasm. They compared the effect of complement activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…The higher CSF levels of C3a and C4a in patients with DIND indicated a relationship between these components and the pathogenesis of cerebral vasospasms. Another earlier study showed that complement activation by aged erythrocytes can result in MAC insertion into “innocent bystander” smooth-muscle cell membranes and that this mechanism may contribute to development of vasospasm after subarachnoid hemorrhage (Park et al, 1997). The earlier dogma that MAC could only attack non-nucleated cells (Whaley, 1987) now seems to be overturned, although it is still not clear what the final contribution of the MAC is to complement-mediated brain injury.…”
Section: The Role Of Complement In Strokementioning
confidence: 99%
“…The higher CSF levels of C3a and C4a in patients with DIND indicated a relationship between these components and the pathogenesis of cerebral vasospasms. Another earlier study showed that complement activation by aged erythrocytes can result in MAC insertion into “innocent bystander” smooth-muscle cell membranes and that this mechanism may contribute to development of vasospasm after subarachnoid hemorrhage (Park et al, 1997). The earlier dogma that MAC could only attack non-nucleated cells (Whaley, 1987) now seems to be overturned, although it is still not clear what the final contribution of the MAC is to complement-mediated brain injury.…”
Section: The Role Of Complement In Strokementioning
confidence: 99%
“…It has been estimated that the range for bystander-induced complement cytotoxicity is ~2.5 ”m [8], which would allow injury of closely intermingled oligodendrocytes following complement activation on astrocytes. There is precedent for complement bystander cytotoxicity for astrocyte injury in Rasmussen’s encephalitis following complement activation by glutamate receptor GluR3 autoantibodies in neurons [36], and for a large increase in membrane conductance of rat cerebral artery smooth-muscle cells caused by complement activation on aged erythrocytes [18]. The experimental evidence here includes cytotoxicity and immunofluorescence in astrocyte-oligodendrocyte cocultures exposed to AQP4-IgG and complement, as well as in rat brain following intracerebral AQP4-IgG administration.…”
Section: Introductionmentioning
confidence: 99%
“…Platelets are also susceptible to immune destruction and may be particularly prone to ‘bystander destruction’, whereby membrane attack complexes non‐specifically injure nearby cells . There is also growing evidence implicating direct platelet interaction with complement proteins as an important regulator of the classical and alternative pathways .…”
Section: Discussionmentioning
confidence: 99%